Оцінка можливостей відновлення кадрового потенціалу НАН України - Попович, О.С.; Костриця, О.П. (Вісник НАН України, 2018)
На основі розробленого авторами методу прогнозування еволюції кадрового потенціалу науки показано, що збереження, а тим більше нарощування
чисельності дослідників НАН України неможливе без істотного зростання
приходу молоді в наукові колективи. Розраховано необхідні темпи такого
зростання для кількох сценаріїв розвитку Академії. On the basis of the method developed by the authors for predicting the evolution of the personnel potential of science it
has been shown that preservation, and even more, the increase in the number of researchers of the National Academy of
Sciences of Ukraine is impossible without a significant increase in the influx of young people into scientific groups, the
rates of such growth necessary for this purpose are calculated for several variants of development.